1931 N.Y. Laws 1033, ch. 435, § 1 - (:unkn) unknown (General Publisher, 1931)
Prohibited using an imitation pistol and carrying or possessing a black-jack, slungshot, billy, sandclub, sandbag, metal knuckles, bludgeon, dagger, dirk, dangerous knife, razor, stiletto, imitation pistol, machine gun, sawed off shot-gun, or ay other dangerous or deadly weapon.
--
Keywords: POSSESSION